2018
DOI: 10.1530/ec-18-0362
|View full text |Cite
|
Sign up to set email alerts
|

Shorter telomeres associated with high doses of glucocorticoids: the link to increased mortality?

Abstract: ObjectivePatients with non-functioning pituitary adenomas exhibit high morbidity and mortality rates. Growth hormone deficiency and high doses of glucocorticoid substitution therapy have been identified as corresponding risk factors. Interestingly, high levels of endogenous cortisol in, e.g., patients with post-traumatic stress disorder or patients with Cushing’s disease have been linked to shorter telomere length. Telomeres are noncoding DNA regions located at the end of chromosomes consisting of repetitive D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
8
2
Order By: Relevance
“…Importantly, increased levels of stress hormone, such as cortisol and glucocorticoids, have been previously reported to have a negative effect on telomere length in peripheral tissues [63][64][65] . Furthermore, the expression of telomerase, the enzyme with the ability to counteract telomere erosion, is susceptible to modulation by different hormones 39,[65][66][67] , including glucocorticoids 68 , thus providing further support for such a molecular mechanism. Interestingly, the balance of cardiomyocyte mr and gr has been shown to be paramount for cardiovascular health in mice 69 , which is consistent with the higher MR:GR ratio found here in aging zebrafish with shorter telomeres.…”
Section: Discussionmentioning
confidence: 96%
“…Importantly, increased levels of stress hormone, such as cortisol and glucocorticoids, have been previously reported to have a negative effect on telomere length in peripheral tissues [63][64][65] . Furthermore, the expression of telomerase, the enzyme with the ability to counteract telomere erosion, is susceptible to modulation by different hormones 39,[65][66][67] , including glucocorticoids 68 , thus providing further support for such a molecular mechanism. Interestingly, the balance of cardiomyocyte mr and gr has been shown to be paramount for cardiovascular health in mice 69 , which is consistent with the higher MR:GR ratio found here in aging zebrafish with shorter telomeres.…”
Section: Discussionmentioning
confidence: 96%
“…Although no RTL difference between CF and HS was identified herein, inhaled corticosteroids associated with shorter RTL. Athanasoulia-Kaspar et al reported that patients with nonfunctioning pituitary adenomas and higher daily cortisol doses had shorter telomeres [29]. Furthermore, an in vitro study showed a considerable reduction (50%) in telomerase activity in T-lymphocytes after exposure to high cortisol levels [30].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Verde et al identified that tobacco consumption caused a reduction in leukocyte telomere length [33]. Furthermore, the use of medications, for instance, glucocorticoids [34] and proton pump inhibitors (PPIs) [35], has been previously shown to induce telomere shortening. Patients with non-functioning pituitary adenomas displaying adrenal insufficiency receiving hydrocortisone replacement have also been shown to have shorter telomeres [34].…”
Section: Relationship Between Telomere Length and Other Risk Factors mentioning
confidence: 99%
“…Furthermore, the use of medications, for instance, glucocorticoids [34] and proton pump inhibitors (PPIs) [35], has been previously shown to induce telomere shortening. Patients with non-functioning pituitary adenomas displaying adrenal insufficiency receiving hydrocortisone replacement have also been shown to have shorter telomeres [34]. Moreover, chronic exposure to esomeprazole impaired endothelial function and accelerated endothelial senescence by reducing telomere length [35].…”
Section: Relationship Between Telomere Length and Other Risk Factors mentioning
confidence: 99%